VD_FINDINFO HC / 2014 / 441 vom 21. Mai 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, NOVA, CONJOINT, ENFANT, OBLIGATION D'ENTRETIEN | 271 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 316 al. 3 CPC (CH), 317 CPC (CH)